The Study on Flood Wave Propagation Using Various Routing Method on Branches Reservoir Surface - Azad W.H.; Hassan A.J.; Mulok S.A.; Ali A.M.; Mohd Sidek L.; Basri H. (Springer, 2023)
Flood forecasting based on the distributed model is becoming popular in Malaysia. It is one of the methods to reduce flood risk when a structural measure is very expensive to implement. Two main outputs from the forecasting model are the timing of the flood wave to arrive in the area of interest and the magnitude of the flood. However, another factor, which needs to be given attention, is the simulation computational time. Flood forecasting model demands a fast and accurate computation. The river channel is normally represented by river cross-section that deployed the full hydrodynamic equation. But when come to modeling a reservoir, three common methods can be applied which are lumped flow routing using pool routing method, 1-Dimensional and 2-Dimensional dynamic wave routing. This paper discusses the significance of the different methods applied to represent the flood wave propagation in branching and nearly full reservoir. Beris Dam reservoir was selected for the analysis. Since no data available for calibration, the assessment is purely analytical. The results show that there are differences of time and magnitude for floodwater to start spilling from the spillway. The simulation time for the pool routing is very short as compared to 1D and 2D. Where this is making attractive for flood forecasting but there is a need in the future to apply the 2D method for a large reservoir. 2020, Springer Nature Singapore Pte Ltd.